Gene ancestries reveal diverse microbial associations during eukaryogenesis - Moisès Bernabeu; Saioa Manzano-Morales; Marina Marcet-Houben; Toni Gabaldón (Nature, 2026)
Abstract The origin of eukaryotes remains a central enigma in biology 1 . Continuing debates agree on the pivotal role of a symbiosis between an alphaproteobacterium and an Asgard archaeon 2,3 . However, the nature, timing and contributions of other potential bacterial partners 4–6 and the role of interactions with viruses 7–9 remain contentious. To address these questions, we used advanced phylogenomic approaches and comprehensive datasets spanning the known diversity of cellular life and viruses. Our analysis provided a revised reconstruction of the last eukaryotic common ancestor (LECA) proteome, in which we traced the phylogenetic origin of each protein family. We found compelling evidence for multiple waves of horizontal gene transfer from diverse bacterial donors, with some likely to have preceded mitochondrial endosymbiosis. We inferred plausible traits of the major donors and their functional contributions to the LECA. Our findings support a contribution of horizontal gene transfers to shaping the proteomes of pre-LECA ancestors and suggest a facilitating role of Nucleocytoviricota viruses. Taken together, our results suggest that ancient eukaryotes may have originated within complex microbial ecosystems through a succession of diverse associations that left a footprint of horizontally transferred genes.